Staphylococcus pettenkoferi Bacteremia: A Case Report and Review of the Literature. Issue 6 (2015) - Hashi, Abdulaziz Ahmed; Delport, Johannes Andries; Elsayed, Sameer; Silverman, Michael Seth
Abstract : Staphylococcus pettenkoferi is a relatively recently described coagulase-negative staphylococci species first described in 2002. Since then, nine additional cases of infection caused by this species have been reported in various countries around the world, including Germany, Belgium, France, South Korea, Italy, Brazil and Mexico. The present report describes a case of S pettenkoferi peripheral line-associated bacteremia. To our knowledge, the present report is the first description of human infection caused by S pettenkoferi in Canada. The present report also provides an overview of the laboratory detection of uncommon coagulase-negative staphylococci.